Single-molecule DNA conductance in water solutions: Role of explicit water-counterion sheath and chemical modification of nucleobases - Starikov, E.B.; Nganou, C.; Lee, K.H.; Cuniberti, G.; Wenzel, W. (2009)
Dependence of charge transmission through several conventional and extended DNA duplexes on the explicit presence of their water-counterion surrounding has been theoretically studied. We show here that: (a) the latter does not form specific charge transmission channels in addition to those available in DNA duplexes themselves; (b) chemically modifying DNA bases to extend their π-electronic systems does not significantly alter time-averaged charge transmission probability through DNA duplexes. ？ 2009 World Scientific Publishing Company.
Keywords: adenosine; counterion; cytidine; DNA; DNA base; double stranded DNA; guanosine; nucleic acid base; purine; pyrimidine; thymidine; water; anisotropy; article; base pairing; chemical modification; controlled study; DNA conformation; DNA modification; DNA structure; electric conductivity; physical chemistry; priority journal; quantum chemistry